Numerical study of stability of coal pillars under the influence of line of extraction. Issue 1 (31st December 2022) - Vinay, Lingampally Sai; Bhattacharjee, Ram Madhab; Ghosh, Nilabjendu; Budi, Gnananandh; Kumar, Jagapthal Vinod; Kumar, Shankar
Abstract: In underground coal mining, strata instability is one of the most catastrophic hazards, which involves sudden and violent dynamic failure of the pillars and overlying strata. Despite decades of research, the contributing factors and mechanisms of failure of underground structures are still not completely understood. Hence, it remains challenging to forecast strata failures and quantify their likelihood of occurrence. This paper deals with the scope of application of different line of extraction in problematic conditions, such as when the pillars are surrounded by goaf areas or are overstressed or there are other transportation/coal evacuation issues. In this paper, the effect of line of extraction on pillar stability has been studied in the context of an Indian underground coal mine by way of a comparative analysis through numerical simulation. The stress on the coal pillars during depillaring have been found to be similar for steep-diagonal line and straight line of extraction. However, stress on the pillars in case of steep-diagonal line follows a better trend than straight line of extraction. Overall, the results of this study establish the scope of application of different line of extraction in geo-mining conditions which do not allow implementing straight line of extraction in mechanised depillaring.